The Attitude of Children and Parents Towards Children Influencers - Izabela Kołaszewska; Agnieszka Kacprzak (Journal of Marketing and Consumer Behaviour in Emerging Markets)
The phenomenon of internet influencers is among the most discussed issues in marketing to children. The amount of time children spend on the internet increases every year, which increases the risk of becoming the target of infl uencer marketing. Studying the impact of infl uencers on children is of great importance not only for marketers, but also for parents responsible for upbringing their off spring. This article presents the results of a qualitative study aimed at describing three components of the attitude (cognitive, emotional and behavioural) of children and parents towards children influencers. The methods employed in this study are focus group interviews and individual in-depth interviews with 18 participants: children aged 8–11 and their parents. During the interviews, one sample YouTube video and two TikTok children influencer videos were presented. The analysis of cognitive aspects of attitude showed that children have a higher level of awareness of product placement in influencer video than their parents suspect. Many parents declare that they are against such content on social media, while children see nothing wrong with promotional content and believe that it is natural. As far as the emotional aspect of attitude is concerned, parents present a wider range of emotions than children, possibly because they are less familiar with such content. Being exposed to product placement in influencer videos also impacts the behavioural aspect of attitude. Children are eager to have the promoted products, but parents are sceptical about such products and declare that they buy them only for special occasions.